Penerapan Chatbot Pada Aplikasi Ujian Penentu Program Studi Di Politeknik Manufaktur Negeri Bangka Belitung - Anugrah, Apri; Fujiyanti, Linda; Mubaroh, Sari (Jurnal Inovasi Teknologi Terapan, 2023)
The State Polytechnic of Manufacturing of Bangka Belitung (Polman Negeri Babel) offers many study programs to attract prospective students, however, interview results show that many of them are mistaken in choosing study programs. The problems identified include students wanting to change study programs, confusion in determining study programs, the level of involvement of others in determining study programs, and the number of students who do not complete their studies. The goal of this final project is to design and build a website-based application for prospective students of Polman Negeri Babel so they do not make mistakes in choosing study programs. The author uses the waterfall method and black box testing as system testing to build this application which will include features of a chatbot and an entrance exam system that can provide recommendations for suitable study programs based on the interests and knowledge of prospective students. It is hoped that this application can help prospective students make wise decisions in choosing study programs and completing their studies until graduation.